Properties of polyurethane foam/natural fibre composite for air conditioning insulation - Khalid, A.M.; Zuhri, M.Y.M.; Hairuddin, A.A.; As’arry, A. (Taylor and Francis Group, 2024)
This study focuses on the fabrication of a biocomposite with insulating properties suitable for application in refrigeration pipe systems. The objective of this study was to utilise coconut husk and rice husk in a 1:1 ratio as reinforcement for flexible polyurethane foam. Biocomposites were made using hand mixing and casting technique reinforcement ratios of 5%, 10%, 15%, 20%, and 25% weight ratios from reinforcement husks. A thermal resistivity test, along with tensile test and water absorption measurements as a function of fibre content, was conducted according to ASTM standards. The study demonstrated that incorporating coconut and rice husks as reinforcement in polyurethane foam significantly improved the tensile properties of the composite material. The composite reinforced with 25% weight has been found to have highest tensile stress. In contrast, the thermal resistivity is observed to decrease as the fibre content is increased. A maximum thermal resistivity at 5% wt was found from the reinforcement. On the other hand, the amount of water absorption of the polymer compound increases with the increase in weight percentage of natural fibres. Based on these results, Flexible polyurethane foam reinforced with coconut husks and rice husks shows a promising solution for use as insulation for air conditioning pipes.